Biplot analysis of diallel crosses of early maturing tropical yellow maize inbreds in stress and nonstress environments - Badu-Apraku, Baffour; Fontem, Lum. A.; Akinwale, R.; Oyekunle, M. (Wiley, 2011)
Appropriate testers are needed as well as information on heterotic patterns of tropical lowland early-maturing germplasm. Diallel crosses involving nine tropical early maturing maize (Zea mays L.) inbreds were evaluated at five locations in Nigeria from 2007 to 2009 under drought stress, when Striga infested, and in optimal growing conditions to examine the combining abilities and heterotic patterns and identify appropriate testers. Results revealed that TZEI 17 was the closest to the ideal tester and may be considered as the best under drought stress, TZEI 23 and TZEI 9 under artificial Striga infestation, and TZEI 13 across growing conditions. No appropriate tester was identified for the optimal growing conditions. Inbreds were placed in three contrasting tester groups under drought stress, and four groups each were placed under Striga infestation and optimal growing conditions and across research environments. Hybrids between inbreds in contrasting tester groups of each research environment are expected to show heterosis. TZEI 23 × TZEI 13 had a superior performance under all research conditions, suggesting that it has a broad adaptation. Classification of inbreds into distinct tester groups was not possible for 33% of the inbreds under drought stress and for 22% when Striga infested, under optimal growing conditions, and across the test environments.